2019
DOI: 10.15252/embj.2019102870
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNA export factor variant initiates piRNA‐guided co‐transcriptional silencing

Abstract: The PIWI-interacting RNA (piRNA) pathway preserves genomic integrity by repressing transposable elements (TEs) in animal germ cells. Among PIWI-clade proteins in Drosophila, Piwi transcriptionally silences its targets through interactions with cofactors, including Panoramix (Panx) and forms heterochromatin characterized by H3K9me3 and H1. Here, we identified Nxf2, a nuclear RNA export factor (NXF) variant, as a protein that forms complexes with Piwi, Panx, and p15. Panx-Nxf2-P15 complex formation is necessary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 81 publications
(165 reference statements)
5
77
0
Order By: Relevance
“…Asterix/Gtsf1 links tRNAs and piRNA silencing of retrotransposons Jonathan J. 15 N NOE values of the near zero or negative indicate substantial disorder in the Nand C-terminal regions flanking the zinc fingers. The linker between the two zinc fingers also have relaxation data compatible with an ordered backbone.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asterix/Gtsf1 links tRNAs and piRNA silencing of retrotransposons Jonathan J. 15 N NOE values of the near zero or negative indicate substantial disorder in the Nand C-terminal regions flanking the zinc fingers. The linker between the two zinc fingers also have relaxation data compatible with an ordered backbone.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Recent work on several of these proteins (including, but not limited to, Panoramix 12 , Nxf2, and Nxt1 [13][14][15] ) has provided a framework for linking the piRNA pathway to deposition of heterochromatic silencing marks. However, many of the molecular and mechanistic underpinnings that govern these connections remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…piRNA pathway factors appear to be expressed during all stages of oogenesis from GSCs to late-stage nurse cells. Recent studies reported several new factors involved in piRNA pathway in ovary, such as Moon, Boot, Nxf3, Panx, Arx and Nxf2 (Andersen et al, 2017;Batki et al, 2019;Dönertas et al, 2013;ElMaghraby et al, 2019;Fabry et al, 2019;Kneuss et al, 2019;Muerdter et al, 2013;Murano et al, 2019;Ohtani et al, 2013;Sienski et al, 2015;Yu et al, 2015;Zhao et al, 2019). These proteins are expressed at a low level in testis and their functions during spermatogenesis have not yet been reported.…”
Section: Dynamic Organization Of Pirna Pathway During Spermatogenesismentioning
confidence: 99%
“…Nxf2 has two LRR regions, an NTF2-like domain, and a UBA domain at the C-terminus. 80) Nxf2 within the complex interacts directly with target RNA transcripts via the first LRR. 80) Asterix/Gametocyte-specific factor 1 (Gtsf1) can also be found in the vicinity of PPNP.…”
Section: Introductionmentioning
confidence: 99%